PENGARUH VARIASI LAJU ALIRAN BLUE GAS TERHADAP PROPERTY KIMIA LAPISAN TIPIS KARBON YANG DIDEPOSISIKAN MENGUNAKAN TEKNIK PLASMA CHEMICAL VAPOR DEPOSITION (CVD) UNTUK APLIKASI BIOSENSOR - Setiana, Mira; Ferawati, Bangkit Ina (Universitas Nusa Cendana, 2025)
[Effect of Variation of Blue Gas Flow Rate on Chemical Properties of Carbon Thin Films Deposited Using Plasma Chemical Vapor Deposition (CVD) Technique for Biosensor Applications] Biosensors are important devices in the field of medical diagnostics. The high cost due to their single-use is a challenge that must be overcome. The solution that can be done is modifying the surface of the biosensor electrode. Modifying the electrode surface is very important in increasing the selectivity and sensitivity of the sensor. Modification of the biosensor electrode surface can be done by depositing a thin layer of carbon. The surface properties of the modified layer determine the performance of the biosensor. This study aims to analyze the effect of the blue gas flow rate on the chemical bond composition of the deposited layer for biosensor applications. The deposition technique used is the Plasma Chemical Vapor Deposition (CVD) Technique. The substrate used is a glass substrate. The main gases used are Blue Gas and Argon Gas. The role of Blue Gas is a carbon source, while Argon Gas is a carrier gas. The Argon gas flow rate is kept constant (25 mL/minute), while the Blue Gas flow rate is varied: 9.6 mL/minute, 24.1 mL/minute, and 48.2 mL/minute. Characterization of the deposited layer is carried out using Fourier Transform Infra-Red (FTIR). The main chemical bonds observed were C=O, and C=C in the resulting carbon thin film. The absorbance intensity of the C=C chemical bond tended to increase at a Blue Gas flow rate of 24.1 mL/min and decreased at a Blue Gas flow rate of 48.2 mL/min. While the C=O chemical bond tended to decrease as the Blue Gas flow rate increased into the chamber.